2013
DOI: 10.1002/adem.201200318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manganese on Microstructure and Mechanical Properties of Cast High Alloyed CrMnNi‐N Steels

Abstract: Within the Collaborative Research Center 799 novel composite materials which consist of a highly alloyed TRansformation-Induced Plasticity/Twinning-Induced Plasticity (TRIP/TWIP) CrMnNi cast steel matrix and a partially stabilized zirconium dioxide (Mg-PSZ) ceramic, referred to as TRIP-Matrix-Composites, are developed. [1] By applying an external load larger than the yield strength, the TRIP steel matrix shows a strain-induced phase transformation from metastable austenite to a 0 -martensite which leads to a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 25 publications
4
26
0
Order By: Relevance
“…The schematic in Figure 9 generalizes the temperature dependence of tensile elongation in austenitic stainless steels [10,15,[38][39][40][41][42][43]. The schematic elongation curve consists of three regions marked I-III.…”
Section: Influence Of Deformation-induced Processes On the Strain-harmentioning
confidence: 91%
See 1 more Smart Citation
“…The schematic in Figure 9 generalizes the temperature dependence of tensile elongation in austenitic stainless steels [10,15,[38][39][40][41][42][43]. The schematic elongation curve consists of three regions marked I-III.…”
Section: Influence Of Deformation-induced Processes On the Strain-harmentioning
confidence: 91%
“…Therefore, the M d γ → α′ temperature may be used to predict the influence of alloying elements on the elongation curve. Tensile tests at various temperatures of austenitic stainless steels with varied amounts of Ni [39,42], Mn [43], Al [15], Cr [23,25,27], C [23,24], and N [25] have confirmed that they shift the peak elongation temperature to lower temperatures. All of the preceding alloying elements except Al are unanimously known to decrease both M d γ → α′ and M s temperatures [54,55].…”
Section: Design Of Austenitic Stainless Steelsmentioning
confidence: 99%
“…The observed behavior was explained by the presence of microstructural regions with different stabilities with respect to deformationinduced a¢ martensite formation caused by the segregation of alloying elements. Tensile elongation near room temperature of low stacking fault energy (SFE) austenitic steels including stainless, [1][2][3][4][5][6][7][8][9] high Mn, [10][11][12][13] and high Ni [14] steels varies in three temperature regimes as follows. At the highest temperature range (regime I), tensile elongation remains more or less constant or exhibits a weak temperature dependence.…”
mentioning
confidence: 99%
“…The loss of ductility caused by the deformation-induced formation of a¢ martensite initiates the regime III of elongation, characterized by reduced elongations at lower temperatures. The large number of investigations in support of the detrimental effect of a¢ martensite formation on the tensile elongation of metastable austenitic stainless steels [1][2][3][4][5][6][7][10][11][12] indicates that any possible contribution to the ductility of a TRIP effect would not be large enough to prevent the loss of ductility below the M d cfia¢ temperature. This has been also suggested by the modeling of the a¢ TRIP effect contribution to the ductility.…”
mentioning
confidence: 99%
“…To ensure a structure free of carbides, an additional solution heat treatment (5) was carried out at 1150 C for 30 min before quenching in water.…”
Section: Manufacturing Methods For the Base Materialsmentioning
confidence: 99%